Lectotype designations, new synonymies, and new species in the genera Trichillum Harold and Pedaridium Harold (Coleoptera: Scarabaeidae: Scarabaeinae) - Vaz-De-Mello, Fernando Z.; Génier, François (Zootaxa, 2005)
Three new synonymies are proposed in the genera Trichillum and Pedaridium (the second epithet is valid): T. pereirai Martínez, 1959 = T. heydeni Harold, 1868; T. boucomonti Saylor, 1935 = T. hirsutum Boucomont, 1928; and P. brasiliense Ferreira & Galileo, 1993 = P. bidens Balthasar, 1938. One previous synonym (T. elongatum Balthasar, 1939 = P. argentinum Arrow, 1913) is confirmed. Lectotypes are designated for three species names (including one synonym): T. heydeni, P. bidens, and T. elongatum. Species previously misidentified as T. heydeni; T. arrowi Saylor, 1935; and T. depilatum Balthasar, 1942 are described as new, respectively T. tishechkini sp. nov., T. pseudoarrowi sp. nov., and T. cordobense sp. nov. Brief diagnosis and illustrations are given for treated species.Três nova sinonímias são propostas nos gêneros Trichillum e Pedaridium (o segundo epíteto sendo válido): T. pereirai Martínez, 1959 = T. heydeni Harold, 1868; T. boucomonti Saylor, 1935 = T. hirsutum Boucomont, 1928; and P. brasiliense Ferreira & Galileo, 1993 = P. bidens Balthasar, 1938. Uma sinonímia anterior (T. elongatum Balthasar, 1939 = P. argentinum Arrow, 1913) é confirmada. Se designam lectótipos para três espécies (incluindo um sinônimo): T. heydeni, P. Bidens, e T. elongatum. Novas espécies previamente erroneamente identificadas como T. heydeni; T. arrowi Saylor, 1935; e T. depilatum Balthasar, 1942 são descritas, respectivamente T. tishechkini sp. nov., T. pseudoarrowi sp. nov., e T. cordobense sp. nov. Se apresentam diagnoses e ilustrações de cada espécie tratada.